Severe bilaterial ventriculomegal y diagnoses in a third trimester fetus: Case report and literature review - Rodriguez-Verduzco, Julio César (2024)
Fetal ventriculomegaly (VM) is defined as an increase in the diameters of the lateral ventricles greater than 10 mm on a prenatal ultrasound. It has an incidence of 0.3 to 1.5 per 1000 births. The ultrasonographic finding generally occurs during the examination in the second trimester, associated with malformations of the central nervous system (CNS), disruptive events or genetic syndromes. Classification in 1 or 2 ways: mild (10-15 mm) or severe (>15 mm), or mild (10-12 mm), moderate (13-15 mm) or severe (>15 mm). A 26-year-old patient, with a preterm pregnancy, poor prenatal control, was admitted with preterm labor. Stable vital signs, single fetus, alive, obstetric ultrasound with report of severe bilateral VM. It was decided to begin a protocol for resolving the pregnancy via an emergency abdominal route, a male newborn was obtained in cardiorespiratory arrest, neonatal resuscitation maneuvers were not provided. This finding is only a preliminary step to take during the diagnostic approach to recognize the cause of ventricular dilation. When no cause is found, it is defined as "isolated", representing, by definition, provisional discrimination of exclusion.